Cellulose production in Pseudomonas syringae pv. syringae: a compromise between epiphytic and pathogenic lifestyles. - Arrebola-Díez, Eva María; Carrión Bravo, Víctor José; Gutiérrez Barranquero, José Antonio; Pérez-García, Alejandro; Rodríguez-Palenzuela, Pablo; Cazorla-López, Francisco Manuel; De-Vicente-Moreno, Antonio (Oxford Academic, 2015)
Genome sequencing and annotation have revealed a putative cellulose biosynthetic operon in the strain Pseudomonas syringae pv. syringae UMAF0158, the causal agent of bacterial apical necrosis. Bioinformatics analyses and experimental methods were used to confirm the functionality of the cellulose biosynthetic operon. In addition, the results showed the contribution of the cellulose operon to important aspects of P. syringae pv. syringae biology, such as the formation of biofilms and adhesion to the leaf surface of mango, suggesting that this operon increases epiphytic fitness. However, based on the incidence and severity of the symptoms observed in tomato leaflets, cellulose expression reduces virulence, as cellulose-deficient mutants increased the area of necrosis, whereas the cellulose-overproducing strain decreased the area of necrosis compared with the wild type. In conclusion, the results of this study show that the epiphytic and pathogenic stages of the P. syringae pv. syringae UMAF0158 lifestyle are intimately affected by cellulose production.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/882
Keywords: Biopelículas; Biopolímeros; Bacterias fitopatógenas; Pseudomonas syringae; Virulence; Biofilm; Woody plants; Phyllosphere; Bacterial EPS